Analysis of Variations in Sleep Patterns Among Pregnant Women and Their Association with the Risk of Premature Birth - Fitria, Henny; Yusriana, Novia; Rahmadi, Elvira (Trigin Institute, 2025)
Premature birth remains a leading cause of neonatal morbidity and mortality worldwide. Emerging evidence suggests that maternal sleep patterns during pregnancy may influence gestational outcomes, yet this area remains underexplored. This study investigates the relationship between variations in sleep patterns among pregnant women and the risk of premature birth. A prospective cohort study was conducted involving 215 pregnant women in their second trimester. Sleep data were collected using the Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), daily sleep diaries, and wrist actigraphy over a two-week period. Participants were followed until delivery, and gestational age at birth was recorded. Logistic regression analysis was used to assess the association between sleep parameters and premature birth, controlling for maternal age, BMI, parity, stress levels, and socioeconomic status. The findings revealed that women with poor sleep quality (PSQI > 5), sleep durations under 6 hours per night, and irregular sleep-wake cycles were significantly more likely to experience preterm birth (p < 0.01). Irregular sleep timing was associated with a 2.3-fold increase in preterm delivery risk. Sleep-disordered breathing symptoms and frequent nighttime awakenings were also more prevalent in the preterm birth group. This study supports the growing evidence that poor and irregular maternal sleep is a significant risk factor for premature birth. These results underscore the need to integrate sleep screening and interventions into routine prenatal care as a preventive strategy to improve maternal and neonatal outcomes.